Collaborative learning processes in the context of a public health professional development program: a case study. Issue 1 (2nd January 2017) - Tremblay, Marie-Claude; Richard, Lucie; Brousselle, Astrid; Chiocchio, François; Beaudet, Nicole
ABSTRACT: The health promotion laboratory (HPL – Canada) is a public health professional development program building on a collaborative learning approach in order to support long-term practice change in local health services teams. This study aims to analyse the collaborative learning processes of two teams involved in the program during the first year of implementation. Based on a multiple case study design involving observations, interviews, and documentary sources, the study: (1) describes the learning process by which each team built a common understanding of the problem at hand and developed an intervention to address it; (2) identifies factors that facilitated or hindered these processes; and (3) proposes a cross-case explanation of the collaborative learning process in the HPL. The results demonstrate that the two teams learned by expanding their repertoire of actions, albeit experiencing different processes. Results point to the central role of shared mental models and key influencing factors, such as commitment and participation (team cohesion), team climate (psychological safety), and leadership style. Unlike previous studies on team learning that concentrated on existing teams in organisations, the current research studied purposely created teams working at transforming their practices and showed that they can successfully learn if specific conditions are achieved.